2019
DOI: 10.1111/cod.13189
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with multiple contact allergies in Thai dermatitis patients: A 10‐year retrospective study

Abstract: Background Multiple contact allergies (MCAs) are defined as three or more positive patch test reactions to unrelated antigens. Factors associated with MCAs include female sex, older age, and certain eczema sites. Objectives To investigate the prevalence of MCAs, risk factors for their development, and patterns of allergen combinations. Methods This retrospective, case‐control study was conducted on patients suspected of having allergic contact dermatitis who had been patch tested with a baseline series in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…These restrictions are expected to positively impact contact allergy rates soon, as evidenced by the declining MI rates in our study and Europe 29 . Regarding multiple contact allergies, both males and females displayed equal outcomes (16%), aligning with our previous study, which concluded that gender was not a risk factor for multiple contact allergies 31 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These restrictions are expected to positively impact contact allergy rates soon, as evidenced by the declining MI rates in our study and Europe 29 . Regarding multiple contact allergies, both males and females displayed equal outcomes (16%), aligning with our previous study, which concluded that gender was not a risk factor for multiple contact allergies 31 …”
Section: Discussionsupporting
confidence: 89%
“…29 Regarding multiple contact allergies, both males and females displayed equal outcomes (16%), aligning with our previous study, which concluded that gender was not a risk factor for multiple contact allergies. 31 We emphasised the importance of patients bringing their PCPs for patch testing, which resulted in a PCP-positive rate of 13% in our study. Regarding patients' PCPs, females tended to use more products, which increased the chances of allergen exposure and the development of contact allergy.…”
Section: Discussionmentioning
confidence: 96%
“…Concomitant positive reactions and polysensitization to the fragrance allergens were also frequently found 21,22 . As illustrated in Figure 1, most patients reacted to only one allergen; however, many of the tested patients had positive reactions to more than one allergen.…”
Section: Discussionmentioning
confidence: 87%